Pemanfaatan E-Commerce Dalam Pengembangan UMKM Kerajinan Tenun Tapis Perspektif Ekonomi Islam Di Kecamatan Kotabumi Selatan - Rumianti, Susti; Eviatun, Esti; Hasan, Saukani (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
This Study aim for know Utilization of e-commerce in Development of Small and Micro Enterprises Medium (MSMEs) Handicrafts weaving Tapis in Subdistrict Kotabumi selatan reviewed in Perspective Islamic Economics. Study this use approach qualitative with method studies case. Technique data collection used is technique interview in a manner depth, documentation, and observation. Data collection and determination informant study use technique purposive and snowball. Research data sources that is using primary data and secondary data. Inspection or data validation using technique triangulation that is triangulation source and triangulation method. Results study this showing that utilization of e-commerce in MSMEs development in Subdistrict Kotabumi selatan enough maximum, the proven with exists effort use of digital media in the form of e-commerce in development effort. Study this also showing that utilization of e-commerce in development of weaving SMEs Tapis reviewed in perspective economy Islam already capable mirrored by weaving SMEs Tapis in Subdistrict Kotabumi selatan. Keywords : e-commerce, development, weaving warehouse , small micro business and intermediate